Language Learning of XI Arts Students in Relation to Home Environment: - (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The purpose of the study is to find out the relationship between language learning (L1) andCognitive Development Home Environment as well. The sample selected for the study comprises 310male and 226 female students of XI Arts of Agra City. Home Environment Inventory by K.S. Mishra (1986)and Achievement Test of Hindi-Grammar by Dr. S.P. Varshney were used as tools to study. Result revealedthat the rewarding, nurturant, permissive behaviour of parents, were found to be significant and positivefactors for achievement of Hindi Grammar for both the sexes. Whereas rejecting, conformity andpunishing behaviour of parents were found to be negative predictions of AHG. In case of girls conformityand punishing behaviour of parents was not found to be significant and value of C.R. related to rejectingbehaviour of parents was found to be significant at 0.05 level.